Analisis Regulasi Diri Santri dalam Pembelajaran Tahfidz Al-Qur’an pada Sekolah Full Day - Zahro, Wafa’ Maulida; Giyoto, Giyoto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine: 1) self-regulation of students who memorize al-Qur'an in learning tahfidz al-Qur'an in full day school programs, 2) dominant factors in influencing self-regulation of students who memorize al-Qur'an. This research method is descriptive qualitative. The research was conducted at TPA Zahrawain Indonesia Pengging Banyudono Boyolali Branch. The research subjects were santri tahfidz al-Qur'an and the research informants were the head of the institution, the ustadzah of the institution, and the guardian of the students. Data collection techniques using interviews and observations. Data validity techniques are data reduction, data presentation, and drawing conclusions. The results showed that: 1) The self-regulation of students who memorized al-Qur'an included three aspects, namely; a) Metacognition which consists of aspects of planning, organizing, and measuring aspects of self-ability, b) Motivation which consists of aspects of self-confidence and self-reliance in memorization, c) Behavior which consists of aspects of moral and ethical self-regulation, selection and environmental utilization. 2) The dominant factor influencing the regulation of students' tahfidz al-Qur'an includes 2 factors, namely; a) Internal factors in the form of behavior consisting of aspects of self observation (assessing self-ability in the form of moral and ethical aspects, selecting, utilizing the environment) and the judgment process (assessing one's ability to socialize well with the environment, limiting oneself) from the environment / association that is wrong / negative) b) External factors in the form of the environment, namely the support from those closest to the students. In conclusion, there are three aspects that become self-regulation of students who memorize the Koran in learning tahfidz al-Qur'an in full day school programs, namely aspects of metacognition, motivation and behavior with two factors that affect the regulation of students, both internal and external factors. of the students. Keywords: Self-regulation, Tahfidzul Qur'an, and full day school program